2019
DOI: 10.1111/cogs.12711
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Mechanisms of Symbolic Number Processing in Adults’ Mathematics and Arithmetic Achievement

Abstract: A growing body of research has shown that symbolic number processing relates to individual differences in mathematics. However, it remains unclear which mechanisms of symbolic number processing are crucial—accessing underlying magnitude representation of symbols (i.e., symbol‐magnitude associations), processing relative order of symbols (i.e., symbol‐symbol associations), or processing of symbols per se. To address this question, in this study adult participants performed a dots‐number word matching task—thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…In contrast to the canonical distance effect, inconsistent findings have been reported in the few studies that have investigated the correlative association between the reverse distance effect and arithmetic abilities. Some studies have found a negative (i.e., the smaller the reverse distance effect, the better arithmetic performance; Goffin and Ansari, 2016), while other studies have found a positive (i.e., the larger the reverse distance effect, the better arithmetic performance; Vogel et al, 2019) or no relationship at all (Orrantia et al, 2019;Vogel et al, 2015;Vogel et al, 2017;Vos et al, 2017). These findings are in contrast to the consistently positive correlations reported for the canonical distance effect.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast to the canonical distance effect, inconsistent findings have been reported in the few studies that have investigated the correlative association between the reverse distance effect and arithmetic abilities. Some studies have found a negative (i.e., the smaller the reverse distance effect, the better arithmetic performance; Goffin and Ansari, 2016), while other studies have found a positive (i.e., the larger the reverse distance effect, the better arithmetic performance; Vogel et al, 2019) or no relationship at all (Orrantia et al, 2019;Vogel et al, 2015;Vogel et al, 2017;Vos et al, 2017). These findings are in contrast to the consistently positive correlations reported for the canonical distance effect.…”
Section: Introductionmentioning
confidence: 70%
“…Numerical order processing has been proposed as a significant predictor of arithmetic abilities (for a review see Lyons et al, 2016). However, research on the relationship between the reverse distance effect (i.e., as an index of numerical order processing) and arithmetic abilities has demonstrated mixed findings: some studies have found negative (Goffin and Ansari, 2016), positive (Vogel et al, 2019) or no relationship (Vogel et al, 2015;Vogel et al, 2017;Vos et al, 2017;Orrantia et al, 2019). In the present work, we provided evidence that the estimates of the reverse distance effect are subject to qualitative individual differences (i.e., not all participants show a reverse distance effect) and that these individual differences can obscure the relationship with arithmetic abilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the second order task (balanced order task), regular, irregular, and non-ordered sequences were included. This task is similar to the task that was presented in Experiment 1 and resembles the tasks in some previous studies (Lyons & Beilock, 2009;Orrantia et al, 2019). We will refer to this order task as the balanced order task because regular and irregular trials were represented equally among the ordered trials.…”
Section: Methodsmentioning
confidence: 98%
“…In the order task, participants have to decide if a sequence is presented in an order or not. Results from previous studies have indicated that there is a strong relation between performance on the order task and arithmetic performance in both children (Attout & Majerus, 2017;Lyons & Ansari, 2015;Lyons et al, 2014;O'Connor et al, 2018O'Connor et al, , 2019Sasanguie & Vos, 2018;Sommerauer et al, 2020;Vogel et al, 2015) and adults (Goffin & Ansari, 2016;Lyons & Beilock, 2009;Morsanyi et al, 2017;Orrantia et al, 2019;Sasanguie et al, 2017;Sella et al, 2020;Vogel et al, 2017Vogel et al, , 2019Vos et al, 2017). However, the mechanisms underlying this relationship remain relatively underspecified.…”
Section: Introductionmentioning
confidence: 99%
“…The role of cognitive graphics and its interpretation increases in various spheres of human activity. For example, in work [1] the option of identification of some mathematical abilities on the basis of the mechanism of the analysis of symbolical information is offered.…”
Section: From Historymentioning
confidence: 99%